Marketing Strategy of Micro Small Medium Enterprises Catering During the Covid-19: Strategi Marketing Usaha Mikro Kecil Menengah Catering pada Masa Pandemi Covid-19 - Setiowati, Efi; Hariyanto, Didik (Universitas Muhammadiyah Sidoarjo, 2023)
Enterprises Catering in the Bluru Permai housing during the Covid 19 pandemic. This study uses the theory of Kotler and Keller 4 P. Product, Price, Place, Promotion. The research method used descriptive qualitative with interview, documentation, observation data collection techniques and analyzed using Miles and Huberman analysis, namely data reduction, data presentation and conclusions.The results of the research are Raya Catering's marketing communication strategy from making more attractive and innovative packaging, as well as making a logo so that it is easy to understand and through social media Instagram with the name @Raya_Cateringsidoarjo. For Fajar Catering owners, the marketing strategy is carried out using social media in the form of Instagram which is uploaded to the Instagram story feed. Putri Rasa's Catering Marketing Strategy through brochures and Instagram social media. Marketing strategy of Catering Metro by word of mouth and watsapp social media.